Modification of Used Rubber Tire Mortar with Fly Ash Addition - Faizah, Restu; Pratama, Putra Andhika Dwi; Wibowo, Prio Arif; Prasetyo, Nugroho Budi; Darmawan, Muhammad Harris; Prasetya, Aryansyah Aditiya; Setioningsih, Retnowati (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
Used tire rubber mortar has been studied for its physical, mechanical, and dynamic properties. Adding used tire rubbers to the mortar is considered effective in improving the brittle properties of the mortar, as well as increasing the mortar's elasticity and damping ability. However, the higher the tire rubber content, the lower the strength of the mortar. Therefore, the use of tire rubber mortar has some limitations. This study investigates the possibility of fly ash as an admixture in tire rubber mortar to enhance its compressive strength. The compressive strength test follows the provisions of ASTM C-109, with a cube-shaped test object measuring 5x5x5 cm3. The specimen type consists of normal mortar, 30%, and 40% tire rubber mortar. Variations in fly ash content are 0%, 5%, 10%, 15%, 20%, 25%, and 30%, respectively. Compressive strength tests were conducted when the mortar was 14, 28, and 56 days. With five specimens for each variation, 245 specimens were tested. The test results show that adding fly ash can be recommended to increase the compressive strength of tire rubber mortar, with a maximum content of 20% by weight of cement. The tire rubber mortar with fly ash mixture experienced a significant strength in 28 – 56 days due to the escalation of fly ash adhesion between the rubber paste and cement.